(untitled) (Delta Medical College Journal, 2015)
Background: Medicinal plants constitute an important source of potential therapeutic agents for diabetes. Objective: In the study, we aimed to investigate the pre-treatment effect or preventive effects of Moringa oleifera (MO) leaves on blood sugar of rats. Materials and method: This experimental study was carried out in the department of Pharmacology and Therapeutics of Sir Salimullah Medical College in collaboration with Bangladesh Council of Scientific and Industrial Research (BCSIR), Dhaka. A total 24 long Evans rats were included in this study and divided in to four groups. Hyperglycemia was induced on rats using alloxan (100 mg/kg body weight, intraperitioneally). Blood sample was collected from tail vein by tail tipping method. Pre-treatment effect or preventive role of Moringa oleifera (drumstick) leaf powder on diabetogenesis produced by Alloxan in rats was tested by giving 50 mg/rat/day Moringa oleifera leaf powder for 14 days orally as pre-treatment along with standard rat feed. Then alloxan was administered intraperitoneally on 15th day of the experiment and 50mg/rat/day Moringa oleifera leaf powder was given for 7 days as post-treatment. Results: No significant effect of MO on blood glucose level was observed on normal rats and non significant hypoglycaemic effect was found in rats that were pretreated with MO. Conclusion: The present study suggests that Moringa oleifera leaf powder did not produce any significant protective effect in diabetogenesis produced by alloxan though it has hypoglycaemic effect. Delta Med Col J. Jul 2015; 3(2): 63-67